Gerontological activism: an example of an intergenerational academic course within a university–community partnership. Issue 7 (3rd July 2018) - Agmon, Maayan; Doron, Israel; Ergon-Karlin, Shlomit
ABSTRACT: This article describes and discusses a novel academic course founded by the Faculty of Welfare and Health Studies at the University of Haifa, Israel, which tried to establish an alternative interaction between graduate students and older persons as part of its graduate academic program. The course "Social Activism and Old Age: From Exclusion to Inclusion" brought together senior citizens from the neighborhoods of the northern city of Haifa and graduate students at the Faculty of Welfare and Health Studies at the University of Haifa. Now in its fourth year, this course has shown that academic education and training in the field of gerontology and aging studies can be shaped in ways which provide meaningful intergenerational learning and that old age activism can be achieved within a broader context of university–community partnership (UCP).